Gis-based modelling of the changes in water level due to flood walls - Parvaneh, Parisa (2010)
Flood control structures may protect an area against flood; however, it may also induce inundation in another area at the same time. One of such structural projects is constructing flood walls along a river reach. This study investigated the effects of these flood walls on the upstream of the protected river reach using a GIS-based modelling approach. The framework developed in this study covered the problems encountered in the implementation of the GIS-based hydraulic models in the regions with insufficient integrated data. The study area covered the reach of Karoon River which is located between the Ahwaz and Farsiat hydrometric stations in Khuzestan Province, Iran. The area was selected primarily due to the current and future development of both the residential and industrial centres along this reach, as well as because of the availability of data for the study area. Ahwaz City, which is located at the upstream of this reach, is frequently subjected to flood and flood-related problems. The flood walls on both river banks at the selected reach were simulated in order to compute any changes in the water level and the flow velocity at the Ahwaz hydrometric station. This simulation approach integrated both the ArcGIS tools and HEC-RAS hydraulic model by interfacing the HEC-GeoRAS extension. The river reach and the required features of the HEC-RAS model were digitized and extracted from Triangular Irregular Network (TIN) in the ArcGIS. Meanwhile, the HEC-RAS model was applied for the existing condition with no flood walls and the model was calibrated with the observed data. The restriction on the widths of river cross sections was carried out for a length of I km using three different methods to represent the flood walls. Based on the findings of the study, the best method was subsequently selected, and this was to use flood walls for the whole reach. Flood walls were added to the model using two different designs. In the first design, the widths of the cross sections along the equal length of the river banks (10 km) were confined by the flood walls at three different distances from the Ahwaz station so as to investigate the effects of these distances. The second design incorporated 30 km continuous flood walls, beginning from 10 km downstream of the Ahwaz station. Changes in the water level and the flow velocity at the Ahwaz station, due to the different lengths of the flood walls and the various distances, were determined and analyzed for seven return periods. The increases in the water level for the first design were found to vary from 0.66 m to 1.44 m, and it reached 2.32 m for 100 years return period in the second design. The resulted charts can aid engineers to make judgments on such flood protection techniques. The framework developed in this study could be used as a prototype simulation method for other rivers and to be implemented for different lengths of flood walls at any distance from any upstream gauge.